Development of a Measurement Tool to Assess the Inpatient Experience in a Tertiary Care hospital - Shashi Rekha, S. D.; Aileen, J. (Prabandhan: Indian Journal of Management, 2018)
Patient experience is a way by which the patient's view about the healthcare system can be measured. It mainly emphasises on the various ranges of interactions between the patients and the system of health care, including the patient care starting from the communication of the doctors, nurses, hospital staff, and other physical facilities. The measurement of patient experience has various kinds of approaches that may be qualitative, quantitative, or mixed. Whatever the approach may be, the strategy for improving the experience of patients is measuring things that matter most to patients, and it acts as an essential component for a successful hospital management strategy. With reference to the Indian healthcare system, improvement in quality of care is challenging because of the unavailability of reliable data and technical backwardness. In the study, the primary questionnaire was developed by the review of globally available tools and studying the work process of inpatient touch point areas of the given tertiary care hospital. Through the analysis, we observed that the developed questionnaire served as a good tool to measure the patient experience. The inpatient experience measurement tool is not intended to be used as a stand-alone questionnaire, but can be modified according to the necessities of the healthcare organizations.